2023
DOI: 10.14740/jmc4101
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Anterograde Gastroduodenal Intussusception Caused by Migrated Percutaneous Endoscopic Gastrostomy Feeding Tube

Abstract: Gastroduodenal intussusception is a critical condition in which stomach protrudes into the duodenum. It is a very rare condition in adults. Most common causes include intra luminal lesions in the stomach including benign or malignant tumors of the stomach. Most common tumors included are gastrointestinal stromal tumors (GISTs), gastric carcinoma, gastric lipoma, gastric leiomyoma, and gastric schwannoma. It is extremely rare to be caused by migration of percutaneous feeding tube.A 50-year-old woman with a past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On CT imaging, gastric intussusception is typically represented as a target-like mass. The concentric bowel wall thickening causes this characteristic layering effect [ 6 ]. Furthermore, the lead point can be found most distal to the intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…On CT imaging, gastric intussusception is typically represented as a target-like mass. The concentric bowel wall thickening causes this characteristic layering effect [ 6 ]. Furthermore, the lead point can be found most distal to the intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Few case reports have shown antegrade gastroduodenal intussusception, coinciding with distal migration of the balloon tip feeding catheter. [ 13 , 14 ] Others have shown cases of retrograde intussusception, coinciding with a repositioning attempt of a distally migrated balloon tip catheter. [ 3 , 4 , 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…case reports have shown antegrade gastroduodenal intussusception, coinciding with distal migration of the balloon tip feeding catheter. [13,14] Others have shown cases of retrograde intussusception, coinciding with a repositioning attempt of a distally migrated balloon tip catheter. [3,4,6] It has been suggested that loose fixation of the feeding tube onto the abdominal wall could result in migration of the balloon tip.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of PEG-J tubes placed using endoscopic clips and surgical sutures found that 7% of all tube placement was complicated by migration [10]. Anterograde migration rarely occurs when sutures anchoring the tube in place erode through the skin, leading to tube dislodgement [11]. Physiologic peristalsis subsequently pushes the tube more distally into the small bowel and, in some cases, can even get into the colon [12].…”
Section: Discussionmentioning
confidence: 99%